PBP4 Is Likely Involved in Cell Division of the Longitudinally Dividing Bacterium Candidatus Thiosymbion Oneisti - Wang, Jinglan (Antibiotics (Basel), 2021)
Peptidoglycan (PG) is essential for bacterial survival and maintaining cell shape. The rod-shaped model bacterium Escherichia coli has a set of seven endopeptidases that remodel the PG during cell growth. The gamma proteobacterium Candidatus Thiosymbion oneisti is also rod-shaped and attaches to the cuticle of its nematode host by one pole. It widens and divides by longitudinal fission using the canonical proteins MreB and FtsZ. The PG layer of Ca. T. oneisti has an unusually high peptide cross-linkage of 67% but relatively short glycan chains with an average length of 12 disaccharides. Curiously, it has only two predicted endopeptidases, MepA and PBP4. Cellular localization of symbiont PBP4 by fluorescently labeled antibodies reveals its polar localization and its accumulation at the constriction sites, suggesting that PBP4 is involved in PG biosynthesis during septum formation. Isolated symbiont PBP4 protein shows a different selectivity for β-lactams compared to its homologue from E. coli. Bocillin-FL binding by PBP4 is activated by some β-lactams, suggesting the presence of an allosteric binding site. Overall, our data point to a role of PBP4 in PG cleavage during the longitudinal cell division and to a PG that might have been adapted to the symbiotic lifestyle.